Toward a high-performance management system in health care, part 4: Using high-performance work practices to prevent central line-associated blood stream infections—a comparative case study. Issue 3 (July 2016) - McAlearney, Ann Scheck; Hefner, Jennifer; Robbins, Julie; Garman, Andrew N.
Abstract : Background: Central line-associated bloodstream infections (CLABSIs) are among the most harmful health care-associated infections and a major patient safety concern. Nationally, CLABSI rates have been reduced through the implementation of evidence-based interventions; thus far, however, hospitals still differ substantially in their success implementing these practices. Prior research on high-performance work practices (HPWPs) suggests that these practices may explain some of the differences health systems experience in the success of their quality improvement efforts; however, these relationships have not yet been systematically investigated. Purposes: In this study, we sought to explore the potential role HPWPs may play in explaining differences in the success of CLABSI reduction efforts involving otherwise similar organizations and approaches. Methodology/Approach: To form our sample, we identified eight hospitals participating in the federally funded "On the CUSP: Stop BSI" initiative. This sample included four hospital "pairs" matched on organizational characteristics (e.g., state, size, teaching status) but having reported contrasting CLABSI reduction outcomes. We collected data through site visits as well as 194 key informant interviews, which were framed using an evidence-informed model of health care HPWPs. Findings: We found evidence that, at higher performing sites, HPWPs facilitated the adoption and consistent application of practices known to prevent CLABSIs; these HPWPs were virtually absent at lower performing sites. We present examples of management practices and illustrative quotes categorized into four HPWP subsystems: (a) staff engagement, (b) staff acquisition/development, (c) frontline empowerment, and (d) leadership alignment/development. Practice Implications: We present the HPWP model as an organizing framework that can be applied to facilitate quality and patient safety efforts in health care. Managers and senior leaders can use these four HPWP subsystems to select, prioritize, and communicate about management practices critical to the success of their CLABSI prevention efforts.